Application of Biomarker Tools Using Bivalve Models Toward the Development of Adverse Outcome Pathways for Contaminants of Emerging Concern. (23rd June 2020) - Khan, Bushra; Ho, Kay T.; Burgess, Robert M.
Abstract: As contaminant exposures in aquatic ecosystems continue to increase, the need for streamlining research efforts in environmental toxicology using predictive frameworks also grows. One such framework is the adverse outcome pathway (AOP). An AOP framework organizes and utilizes toxicological information to connect measurable molecular endpoints to an adverse outcome of regulatory relevance via a series of events at different levels of biological organization. Molecular endpoints or biomarkers are essential to develop AOPs and are valuable early warning signs of the toxicity of pollutants, including contaminants of emerging concern. Ecological risk‐assessment approaches using tools such as biomarkers and AOPs benefit from identification of molecular targets conserved across species. Bivalve models are useful in such approaches and integral to our understanding of ecological and human health risks associated with contaminant exposures. We discuss the value of using biomarker approaches in bivalve models to meet the demands of twenty‐first‐century toxicology. Environ Toxicol Chem 2020;39:1472–1484. © 2020 SETAC